Developing Marketing Strategy for Used Car Business Post Pandemic: Case Study of Mobil88 Semarang - Kwan, Vincent; Aprilianty, Fitri (Journal of Consumer Studies and Applied Marketing, 2023)
The used car industry has a fairly good market in Indonesia. 2020 the used car market collapsed due to Covid-19 but began recovering in 2021. Unfortunately, Mobil88 Semarang did not experience this sales surge, instead seeing a 42% sales loss in 2021. The main problem is the ineffectiveness of Mobil88 Semarang's marketing strategy, which results in low brand awareness and market penetration. Therefore, this research aims to develop a creative, effective, and competitive marketing strategy for developing Mobil88 Semarang. This study included external and internal analysis, which will be summarized in the SWOT analysis. This study will employ both qualitative and quantitative research methods. The qualitative approach is utilized to collect in-depth data by interviewing the head of the Mobil88 Semarang branch, existing customers, and potential customers of Mobil88 Semarang. The data obtained from qualitative methods were analyzed using open coding. In addition, a quantitative approach using a questionnaire is applied in this study to validate several concerns. Creating a buyer persona, leveraging social media platforms, and developing cashback programs are among the recommendations for Mobil88 Semarang to solve the company's main issues.